Conceptions on the Teaching of Subtraction: A study Focused on an in-Service Teacher Training Course - Mario Martínez Silva; Núria Gorgorió i Solá (Universidad Autónoma de Baja California, 2004)
This paper reports a research about a group of in-service teachers working in primary public schools in a poor urban zone in Monterrey city, Mexico. Its main aim was to study teachers' conceptions about the teaching of subtraction and, in particular, to know more about the role that they assign to context and contextualizing in the teaching process. Broadly speaking, the research arose from the interest to know more about the relationship between the training and education in mathematics of primary teachers and how the teaching and learning of mathematics actually takes place at school.